2006
DOI: 10.1128/jvi.00270-06
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arginine 332 Allows Human TRIM5α To Bind Human Immunodeficiency Virus Capsids and To Restrict Infection

Abstract: Human TRIM5␣ (TRIM5␣ hu ) only modestly inhibits human immunodeficiency virus type 1 (HIV-1) and does not inhibit simian immunodeficiency virus (SIV mac ). Alteration of arginine 332 in the TRIM5␣ hu B30.2 domain to proline, the residue found in rhesus monkey TRIM5␣, has been shown to create a potent restricting factor for both HIV-1 and SIV mac. Here we demonstrate that the potentiation of HIV-1 inhibition results from the removal of a positively charged residue at position 332 of TRIM5␣ hu. The increase in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
145
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 29 publications
12
145
0
1
Order By: Relevance
“…TRIM5α restriction is species-and virus-specific, and the specificity of restriction is largely determined by interactions between the C-terminal SPRY/B30.2 domain and the intact retroviral capsid. Although structural details are still lacking, mutational studies and sequence analyses of different SPRY alleles have provided insights into the determinants of capsid recognition (e.g., see [138][139][140][141]). In TRIM-Cyp, the SPRY domain of TRIM5α is replaced by cyclophilin A (CypA), a well-known peptidyl prolyl isomerase.…”
Section: Capsid Restrictionmentioning
confidence: 99%
“…TRIM5α restriction is species-and virus-specific, and the specificity of restriction is largely determined by interactions between the C-terminal SPRY/B30.2 domain and the intact retroviral capsid. Although structural details are still lacking, mutational studies and sequence analyses of different SPRY alleles have provided insights into the determinants of capsid recognition (e.g., see [138][139][140][141]). In TRIM-Cyp, the SPRY domain of TRIM5α is replaced by cyclophilin A (CypA), a well-known peptidyl prolyl isomerase.…”
Section: Capsid Restrictionmentioning
confidence: 99%
“…For instance, TRIM5a rh with an arginine at this position instead of a leucine was still fully able to restrict HIV-1. 35 Li et al 36 constructed the reciprocate R335L mutation of TRIM5a hu and found that it weakly inhibited HIV-1; in addition, the double-mutant R332P/ R335L restricted HIV-1 less efficiently than R332P alone. Therefore, isolation of an Arg335 mutant in our screen was rather unexpected.…”
Section: Targeted Mutagenesis Of Arg332 and Arg335 Within Pryspry Firmentioning
confidence: 99%
“…36 Although the protection provided by mutations at position 332 was strong (10-to 30-fold), these mutants still restricted HIV-1 10-times less efficiently than TRIM5a rh did. 36 Numerous gene therapy clinical trials for the treatment of AIDS have been undertaken to mostly disappointing results, both in terms of viral load and of CD4+ T cells counts. 38 In particular, although it is desirable that transgene-expressing cells survive and proliferate in the recipient patients, the opposite is often observed.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations